THE CONFRONTATION OF EDUCATION AND CUSTOMARY LAW AT SCHOOL: THE CASE OF ROMA GIRLS: Faculty of Philosophy, Institute of Educational Sciences, Vilnius University , Universiteto str. 3, LT-01513 Vilnius, Lithuania - ŽEMAITĖLYTĖ-IVANAVIČĖ, INGRIDA (Journal of Education Culture and Society, 2020)
Aim. The main goal of the article is to generalise and describe the aspects revealed during the ethnographic research conducted in 2018 that are related to the gender of Roma girls, as representatives of ethnic group, which have influence on the process of education in the context of school community. Concept. During the ethnographic research conducted in one of the schools in Lithuania in 2018, the fragments of Romani customary law were revealed, which are directly related to the female gender and show how belonging to a certain gender can have impact on the process of education at school. The Roma students were observed in their daily learning and communication environment, i.e. at school. The ethnographic research helped to reveal the ways a Roma school student thinks (interview method) and behaves (observation method) in a basic school. The present research was based on anthropological methodology (Okely, 2002; Bhopal & Myers, 2008; Durst, 2010) and mainly focused on one case-study. Conclusion. The Roma girls in the research acknowledged that life of Roma men is easier and that a heavy burden is placed on the shoulders of girls, what often hinders their successful learning. The burden mentioned by the Roma girls is related to responsibilities in housework and family. She is accompanied by the pressure of community to start a family early: to get married and to give birth to children and, thus, to emphasise and confirm own belonging to this ethnic group and continuation of traditions. The situation is exacerbated by the stereotypes in society and the Roma community, which in most cases are ruthless towards Roma girls and women. Cognitive value. The patriarchate, as the basis of Romani culture, and the unwritten customary law accompanying it frequently become a source of ambiguity. The Roma people, as an ethic group, draw a very distinct boundary between the understanding of "we" and "they", i.e. "the Roma people" and "gadje". Being a non-Roma researcher, i.e. gadje, one faces a difficult challenge - not to make mistakes interpreting various aspects of Romani culture, especially such sensitive ones as gender, gender roles and inequality. However, it becomes easier evaluating indisputable facts: the Romani customary law has influence on the process of their children’s education. Roma children (girls in particular) still abandon the system of education too early (from our, gadje, perspective). EU documents (European Union Agency for Fundamental Rights [FRA], 2014) indicate that more Roma girls than boys indicate the fact of marriage or pregnancy to be the reason for early school leaving. The academic discourse, feminist anthropology allows for particularly critical evaluation of processes.